Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 6. Beitrag. Diptera: Conopidae. - Chvála, Milan (Contributions to Entomology = Beiträge zur Entomologie, 1963)
The above publication deals with the family Conopidae (Diptera). The material collected by the expedition of the Deutsches Entomologisches Institut contained 24 specimens of this family, representing 7 species, 6 of which were new to the fauna of Albania.